THE INFLUENCE OF CUSTOMER RELATIONSHIP MANAGEMENT ON CUSTOMER LOYALTY - Aliya Naura Fakhirah; Muhamad Rizal; Mas Rasmini (Universitas Nusa Cendana, 2025)
This study aims to examine the influence of Customer Relationship Management (CRM) on customer loyalty. The research is conducted quantitatively, with a descriptive explanatory design and a survey research type. The study uses the entire population, consisting of 150 resellers, as respondents. Data was collected through interviews, questionnaires, and literature studies. The data analysis conducted includes multiple linear regression, t-tests, F-tests, and coefficient of determination tests. The results of the study show that the people aspect of CRM, the process aspect of CRM, and the technology aspect of CRM have a positive and significant influence on customer loyalty. The people, process and technology aspects of CRM simultaneously have a positive and significant influence on customer loyalty. This research is still limited to CRM variables and customer loyalty, so further research is recommended to add other variables as independent variables so that it can determine what other factors influence customer loyalty. Keywords: Customer Relationship Management (CRM); People; Process; Technology; Customer Loyalty